Monetary Operations and Islamic Banking in the GCC : Challenges and Options - Basu, Ritu (IMF Working Papers; Working Paper ;, 2015)
The assessment provides evidence of market segmentation across Islamic and conventional banks in the Gulf Cooperation Council (GCC), leading to excess liquidity, and an uneven playing field for Islamic banks that might affect their growth. Liquidiy management has been a long-standing concern in the global Islamic finance industry as there is a general lack of Shari'ah compliant instruments than can serve as high-quality short-term liquid assets. The degree of segmentation and bank behavior varies across countries depending on Shari'ah permissibility and the availability of Shari'ah-compliant instruments. A partial response would be to support efforts to build Islamic liquid interbank and money markets, which are crucial for monetary policy transmission through the Islamic financial system.This can be achieved, to a large extent, by deepening Islamic government securities and developing Shari'ah-compliant money market instruments.